Link Between Electroacupuncture Stimulation near the Sympathetic Trunk and Heart Rate Variability - Kazufumi Takahashi; Xiaoming Wang; Daiyu Shinohara; Kenji Imai (Medical Association of Pharmacopuncture Institute, 2022)
Background : The cardiovascular system and airway smooth muscles are regulated by the autonomic nervous system. Objectives: This study investigated the effect of electrical acupuncture stimulation near the cervical sympathetic ganglia on heart rate variability and respiratory function. Methods : This prospective, single-center study at Teikyo Heisei University recruited 24 healthy adults randomly assigned to no-stimulation and electroacupuncture (EA) groups in a crossover trial with a 2-week washout period. After 5 min of rest, a 5-min rest or acupuncture stimulus was delivered, followed by a further 5 min of rest for both groups. EA, at 2-Hz (level of no pain), was delivered near the left cervical ganglia at the level of the sixth cervical vertebra in the EA group. Results : The high-frequency component of the heart rate variability was significantly higher in the EA group than that in the no-stimulation group. Further, there was a significant increase in the high-frequency component of the heart rate in the EA group during the stimulation compared to before and after stimulation. Heart rate decreased significantly during EA compared to before stimulation in the EA group. Regarding respiratory function, forced vital capacity, forced expiratory volume in 1 s, and peak flow significantly increased in the EA group compared with the no-stimulation group, and after stimulation compared with before stimulation. Conclusion : Stimulation with 2-Hz EA near the cervical sympathetic trunk increased parasympathetic nerve activity and reduced heart rate. However, the respiratory function was activated via increased sympathetic nerve activity. Therefore, 2-Hz EA may be effective for autonomic nerve regulation in bronchial stenosis.